NETRALITAS MEDIA MASSA ERA KINI - Kartinawati, Erwin (KOMUNITAS, 2013)
ThisÂ  paperÂ  isÂ  toÂ  highlightÂ  theÂ  reformationÂ  ofÂ  press freedomÂ  inÂ  termsÂ  ofÂ  theÂ  principleÂ  ofÂ  media neutrality. Neutral, impartial or affiliated with stakeholders, and political power is one thing thatÂ  is a principleÂ  inÂ  theÂ  massÂ  mediaÂ  becauseÂ  theÂ  mediaÂ  mustÂ  maintainÂ  itsÂ  neutralityÂ  asÂ  aÂ  functionÂ  ofÂ  social control and educator. If the period before the reform, freedom of the press overshadowed by âbredelâ or censorship, freedom apparently it isÂ  still not fully considered in the present era. Freedom of the press is now just snatched away by its own internalmedia. If the first media workers have to struggle toÂ  escapeÂ  fromÂ  theÂ  politicalÂ  repressionÂ  ofÂ  theÂ  ruler,Â  nowÂ  mediaÂ  workersÂ  shouldÂ  striveÂ  toÂ  avoid repression owners of capital with all the interest surrounding it, in order to realize the press that truly fair and responsible. Understanding and awareness of the owners of capital or management, at least for one word and one bow to actually enforce the primary purpose of journalism, not only for profit but noble responsibility to the community that is adream to realize a good Indonesian press.